Antibacterial Property of Aloe vera Plant Extract - Esumeh, F. I.; Osagie, R. N.; Agbonlahor, D. E.; Akpe, A. R. (Biological Sciences - PJSIR, 2007)
The an ti bacterial activity of Aloe vera ( barbadensis Miller) was i nvesti gated on some test organism s u si ng th e agar d iffusion and t u be d i l u ti on methods . Et h an ol , hot wat er a nd d i st i l l ed water were the sol vents used for extract i on of t h e active i ngredients from th e pl ant leaf. The test organisms used were Strept ococcus pyogenes, St ap hylo coccus aureus, Pseudomonas aerugin.osa , Ba cillus sp ., K lebsiella sp . , and Eschtirich ia coli . Th e re sult s sh owed tha t Al oe vera cth an ol i c extract h ad more an tibacteri a l act i v i ty t h an the hot water an d d i st il l ed w ater extracts prod uci n g th e l argest zon e of i nhi bition (22 mm) on S. aureus. Th e resu lt s al so show ed that al l t he o rgan i sms tested were suscepti bl e t o th e ext r acts ex cept £. coli, wh ich was r esi stant to th e col d d i sti lled water extract. For su sceptible stra i n s, th e d i ameter of zon es of in h i bition rang ed from 9 mm - 22 mm . Th e resu l t s of th e su scep ti b i l i ty test s sh owed that th e A . vera pl an t extracts com pared favou rab l y w i th t ested commercial an ti bi oti cs. The m i n i m u m i nh i b i to r y concentratio n (MI C) resu l ts reveal ed that th e p l ant ex t racts had l ow MI C val u es, ran ging from 0 . 1 5625-0.625 µg/1111.